Pengaruh Variabel Moderator Pemberdayaan dan Pendayagunaan Zakat dalam Menanggulangi Kemiskinan - Joko Hadi Purnomo (Maliyah : Jurnal Hukum Bisnis Islam, 2019)
The research objective was to determine the effect of zakat empowerment on poverty alleviation, the effect of zakat management on zakat empowerment, zakat management through zakat empowerment on poverty reduction, zakat management on zakat utilization, the effect of zakat utilization on the prevention. poverty, the effect of zakat management through the utilization of zakat on poverty reduction. The approach of this research is a mix method. The research procedure, in the first stage, uses a quantitative method. the second stage uses qualitative methods. The quantitative method uses Structural Equation Model-Partial Least Square analysis. Meanwhile, qualitative analysis uses interactive analysis. The research results prove that: zakat empowerment affects poverty alleviation in East Java Province; Management of zakat affects the empowerment of zakat; Management of zakat through the utilization of zakat has an effect on poverty alleviation; Zakat management has an effect on the utilization of zakat. The Zakat Economic Empowerment Program is proven to be able to turn the mustahiq /poor into muzaqi.